PENENTUAN TINGKAT BUTA WARNA DENGAN METODE SEGMENTASI RUANG WARNA FUZZY DAN RULE-BASED FORWARD CHAINING PADA CITRA ISHIHARA - Nur Hamid; Kusworo Adi (Youngster Physics Journal, 2015)
Color blindness is a condition in which a person can not distinguish certain wave light that can be distinguished by the normal eyes. Tests are currently being used (Ishihara Test and the Farnsworth Munsell) are simple. But, both of them have weakness in the form of test media used and requires appropriate room.       In this study, applies image processing to the development of color blindness level determination. Image processing is done by segmenting the pattern first with fuzzy color space segmentation. Having obtained the pattern of Ishihara image is used, then recombined with the initial image, so that the image obtained Ishihara with a segmented pattern. If the patient is able to see the pattern which is purposed, then continued to another image. However, if the patient can not see the pattern, then the pattern will be increased intensity of red, green and blue. By using a rule-based forward chaining, the determination of color blindness level is determined by the rules of the increase in the intensity of red, green and blue.          The research data is algorithm testing data which is created toward patients. Successful testing is done with total validation (normal patients and color deficiency) 97.8% and validation for diagnosted patients testing contained 85.7% of color deficiency. In the proposed algorithm is also used for the determination of the boundary wavelength capable of being viewed by people with color blindness.               Keywords: color blindness level, color segmentation, enhancements of color intensity